School-Parent Partnership Management Patterns in Improving Student Educational Services at Junior High Schools in North Siberut District, Mentawai Islands Regency - Ranti Marie; Setya Raharja (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the partnership between schools and parents at junior high schools in North Siberut Subdistrict to improve educational services at junior high schools in North Siberut Subdistrict, Mentawai Islands Regency. This study employs a descriptive qualitative approach conducted at SMP N 1 and SMP N 4 in Siberut Utara Subdistrict, with a sample of 42 informants comprising 2 school principals, 16 teachers, 2 committee members, 9 parents, and 13 students. Data were collected through semi-structured interviews, observations, and document analysis. Data analysis was conducted through a triangulation process, encompassing data collection, data reduction, data display, and conclusion drawing or verification, while maintaining the authenticity of information obtained from primary sources and validators. The study found that the partnership was implemented through planning, implementation, and evaluation involving active communication, the school committee, and parents. The main obstacles stemmed from geographical conditions, limited transportation and infrastructure, parents’ busy schedules, and psychological factors such as feelings of inferiority. To address these, the school strengthened communication, conducted home visits, provided counseling, involved the committee, and reported on student progress regularly. Strategies to optimize the partnership were implemented through communicative, collaborative, digital, and conventional approaches, as well as those rooted in local culture, to ensure that support for students’ education remains strong and sustainable.